Estudio de las deficiencias nutricionales en bananeras tecnificadas y semitecnificadas en la zona Machala - Sánchez Burneo, José Alberto (2005)
The study of the nutritional deficiencies was analyzed in a technified and semitechnified banana farm of the Machala area, of El Oro prov-ince, Ecuador. The objectives were: 1. to determine the lacking symptoms of nutrition existent in banana plantations in the area of Machala, at the end of the winter season of 2005, 2. To locate the nutritional deficiencies in the canton, according to the MAG, and; 3. To propose recommendations to overcome the nutritional deficiencies found. It was interviewed at 60 producer of the area, for the obtain-ing of results the area was divided in five groups with relationship to establish by the Ministry of Agriculture and Cattle or proprietors with at least an extension of 10 ha of technified and semitechnified farms. The following results were obtained: The earth holding stays under the regime of private property with an average of 87,5 %. The banana producers realize a soil analysis once a year 73 %, with a low average of 22,6 % as for the analysis and they don't have a fertilization calen-dar. The foliar fertilization is taken advantage in 3 sectors when it was applied products for the control of black Sigatoka, and it was make in aerial form with 84,2 %. Among the aspects that favor the agriculture is the use of main fertilizers as N-P-K with 92,2 %, 84,8 % and 84,1 % in their order, with lacking in the whole area of the microelements use (Mg, S, Ca, Zn, B, Mn, Fe) in 28,3 % and exist resistance to use of organic fertilizer. The nutritional deficiencies identified in the plantations as for macroelements the general average obtained a weakness of 45,6 % and it for microelements of 33,8 %. The technology applied in the farms by the banana producers is based on own experience, existing changes important, but they don't have tech-nique with the use and abuse of chemical and handling of soil.